Weight underestimation and body size dissatisfaction among black African adults with obesity: Implications for health promotion - Kufre J. Okop; Naomi Levitt; Thandi Puoane (AOSIS, 2019)
Background: Body image perception has an impact on modifiable cardiovascular disease (CVD) risk, lifestyle and psychological health in many populations. Aim: To assess weight discordance (underestimating own weight) and body size dissatisfaction (perceiving body size as either 'too small' or 'too large') among overweight and obese South Africans, the associated factors and the implications for health promotion. Setting: A rural community and an urban township in two provinces of South Africa. Methods: An ancillary study within a prospective cohort involving 920 adults aged 35-78 years. Information on body image perception, anthropometry, risk factors and weight change were obtained on year 4 follow-up. Obesity was described as having a body mass index (BMI) 25 kg/m2. Descriptive and multivariate analyses were undertaken. Results: Most obese and overweight adults, respectively, underestimated their own weight (85% vs. 79%) and considered their body sizes as either 'too large' (59%) or 'too small' (57%). Those who perceived CVD threat, compared with those who did not, were 3.0 times more likely to be dissatisfied with their body sizes (p 0.0001) and 1.6 times more likely to underestimate their own weight (p 0.001). Those who indicated their willingness to lose weight were seven times more likely to be dissatisfied with their body sizes and unlikely to have discordant weight status (p = 0.0002). Conclusion: Body size dissatisfaction and weight underestimation were influenced by perceived threat of CVD and the willingness to lose weight. Obesity prevention should leverage on perceived CVD threat messaging and self-motivation for attaining a healthy weight.